Projeto, estudo e construção de uma microrrede experimental para testes de equipamentos e controle - NASCIMENTO, Alyston Claydson Veríssimo do (2022)
Since the increasing interest in the use of renewable energy sources, several researches have been carried out to enable and integrate the various systems of electric energy generation into the grid. In this context, microgrids have been widely studied and implemented. This is due to the flexibility regarding the fields of application, which can be composed of power sources such as solar, wind, diesel generation, and to generally composed of energy storage systems. The controls of a microgrid are intended to meet the conceptual design assump tions regarding the global management system, being essential for the continuous supply of electrical energy. They are important for coordinating the power sources, renewable or dispatchable, the storage system, and the power converters. In general, these controls are implemented in Programmable Automation Controllers (PAC). All microgrid control is im plemented in the PAC, which establishes communication with all microgrid components that must be controlled. In addition to control strategies, one of the difficulties in developing and implementing a microgrid is the communication system. This is due to the fact that the various components composing it may come from different manufacturers. Outing to this, the communication protocols and hardware of the equipment are the most diverse. In this context, this work focused on the study and implementation of a microgrid, as well as the development of control strategies for applications in system management and monitoring. One of the implemented strategies was based on a solution for charging the battery bank from a dispatchable source, taking into account the dynamics of a microgrid disconnected from the utility grid. Furthermore, the study and development of low-cost hardware and software, such as open-source, from which it was possible to propose solutions for integrating non-standard communication. In order to validate this research, the communication system, and the microgrid control and management strategies were tested in a real microgrid, namely the one installed in Ilha Grande. Also, the entire communication infrastructure was built at the Electric Energy Institute of the Federal University of Maranhão (IEE-UFMA), as well as the PAC, power converters, solar panels, a network emulator, a bank of batteries and a bidirectional converter for the operation of an experimental microgrid. One of the intended objectives with this micro-network is to allow and make future research available to the group of students and professors at the IEE-UFMA. Keywords: distributed generation; microgrids; power electronics